Effect of wrestling exercise on oxidative DNA damage, nitric oxide level and paraoxonase activity in adolescent boys - Hamurcu, Z.; Saritas, N.; Baskol, G.; Akpinar, N. (Pediatric Exercise Science, 2010)
The objective of the current study is to determine the effects of regular wrestling exercise oxidative DNA damage and antioxidant parameters. The findings of the current study have shown that 8-hydroxy-2`-deoxyguanosine (8-OHdG) obtained from wrestlers in basal status were significantly lower than those of sedentary (p = .001). In contrast, Nitric oxide (NO) and Paraoxonase-1 (PON1) were remarkably higher in wrestlers in basal status than those of sedentary (respectively, p = .001, p = .024). While the NO of wrestlers increased immediately after a 1.5-h exercise compared with those before exercise (p = .002), no differences was found between before and immediately after a 1.5-h exercise in 8-OHdG and PON1 (respectively, p = .777, p = .408).Statistically significant correlations were found between the NO and PON1 in the wrestlers in basal status (r = .671, p = .002). In conclusion, our study suggests that wrestling exercise for a healthy life is important in that it reduces DNA damage as well as enhancing antioxidant parameters.